O papel do direito urbanístico na sociedade potencializadora de desastres - Amaral, Marcia do (Universidade do Vale do Rio dos Sinos, 2013)
Disasters recorded recently in Brazil were caused by floods and landslides. Nevertheless the occupation of risk areas is a determinant factor for turning a climatologic event into the condition of a disaster. Especially the magnitude of the damage caused by disasters is directly connected to the illegal occupation of Permanent Preservation Areas unsuitable for housing precisely because they act as a "green infrastructure", providing protection against disasters. Thus, the risk society acts as a potentiator, creating scenarios for future disasters. The present study deals with the description of disasters and their resonances in law based on the observation of the complexity of contemporary society and the impacts of extreme weather events that reflect on all social systems, affecting politics, economy, society, law. This reality demands transformations to the State and the Law in orther to manage disaster risk, with highlight to the relevance of local public policies and to compliance with urban codes for implementing the management cycle of the National Protection and Civil Defense Policy, which encompasses prevention, mitigation, preparedness, response and recovery actions.
Keywords: Direito urbanístico; Prevenção; Desastres; Vulnerabilidade; Gestão de riscos urbanos; Urban law; Prevention; Disaster; Vulnerability; Urban risk management; ACCNPQ::Ciências Sociais Aplicadas::Direito